Uso de animales en docencia; percepción de los estudiantes - Granados Zúñiga, Jorge (2007)
The still necessary use of animals in physiology instruction requires an adequate attitude by students. Until now there’s no information on the way medicine students perceive the use of animals in their courses. The main objective of this study was to measure that perception on a group of medicine students from the Universidad de Costa Rica.A questionnaire on students’ personal information, their expertise or previous information on use of animals and their knowledge on final disposition of animals was applied.At moment of enquiry 98% of students (n=88) already had used animals in some academic activity; despite 73% of them knew the existence of regulations on the use of animals only between 2-36% knew where the animals came from or where did they go after they were used. Finally, regardless 89% of the students thought that the use of animals provides some benefit to their learning they also saw such a practice with no advantages or with disadvantages. It is recommended the use of alternative methods as substitution or complement of animals in physiology teaching.